2010
DOI: 10.1007/s12350-010-9214-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight on long-term survival among patients without known coronary artery disease and a normal stress SPECT MPI

Abstract: In patients without known cardiac disease and a normal stress SPECT, overweight and obese patients had a lower rate of all-cause mortality compared to normal weight patients over long-term follow-up. This study substantially extends the spectrum of patients in whom the obesity paradox is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
10
1
2
Order By: Relevance
“…3 In contrast to results of previous studies from the broad population of ACLS participants, in the current study of ACLS men with known or suspected CHD, overweight men had a lower risk for all-cause mortality compared with their normal-weight counterparts, and the pattern of association was similar whether WC or percent BF was used as the adiposity exposure. Furthermore, men with higher levels of WC, percent BF, or BMI up to 35.0 kg/m 2 had CVD mortality risks that did not differ significantly from those of their respective reference groups.…”
Section: Discussioncontrasting
confidence: 94%
“…3 In contrast to results of previous studies from the broad population of ACLS participants, in the current study of ACLS men with known or suspected CHD, overweight men had a lower risk for all-cause mortality compared with their normal-weight counterparts, and the pattern of association was similar whether WC or percent BF was used as the adiposity exposure. Furthermore, men with higher levels of WC, percent BF, or BMI up to 35.0 kg/m 2 had CVD mortality risks that did not differ significantly from those of their respective reference groups.…”
Section: Discussioncontrasting
confidence: 94%
“…15,17,18 In a large meta-analysis in patients with known CAD, cardiovascular and all-cause mortality rates were lower in overweight and mildly obese patients compared with patients with normal BMI. 8 Data from the Lipid Research Clinics Study 19 and Aerobics Center Longitudinal Study 20 demonstrate that fitness level was a stronger predictor of mortality than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In 13 of the studies, the distribution of men and women was reported in a total of 91,063 patients, 68% of whom were male. In only three studies were women considered separately (Curtis et al, 2005;Uretsky et al, 2007Uretsky et al, , 2010. Obesity paradox was evident in all of these studies, representing a total of 15,918 women.…”
Section: Paradox #1: Classic Obesity Paradoxmentioning
confidence: 99%